Is It a Benefit Using Robotic Process? Automation in Supply Chain Management? - Elena PUICA (Communications of International Proceedings, 2021)
The automation of operations within the supply chain management (SCM) is maintained with increased evolution, each part of supply chain management is being affected by the digital transformation and the challenge to become more agile, efficient, and dynamic. To consistently achieve performance supply chain management (SCM) must focus on higher-value activities that lead to significant results. The automation of low-value activities is important for the continuity and sustainability of supply chain management (SCM) and at the same time to provide better results. Through software robots, omissions that would result from manual processing of SCM activities can be removed. Software robots can exclude downtime by archiving and maintaining a history of actions performed. Software robots work 24 hours/7 days and can be implemented quickly because they can work on the existing architecture of programs that are already used in SCM. Robotic Process Automation (RPA) can be trained and prepared by users to undertake repeatable structured tasks that interact at the same time with multiple computer systems. The article considers the definition of RPA and its benefits in SCM, the use of RPA within SCM, as well as an example of the applicability of RPA in supply chain management.
Keywords: Robotization of Business Processes1; Robotic Process Automation (RPA)2; Software Robots3; RPA in SCM4; RPA Solutions5; Intelligent Process Automation6; Informatic Solutions in SCM7